2018
DOI: 10.1503/cjs.006917
|View full text |Cite
|
Sign up to set email alerts
|

Associations between provider and hospital volumes and postoperative mortality following total hip arthroplasty in New Brunswick: results from a provincial-level cohort study

Abstract: Our results suggest that patients admitted for hip replacements in New Brunswick can expect to have similar risk of death regardless of whether they are admitted to see a provider with high or low THA volumes and of whether they are admitted to the province's larger or smaller hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Three studies [21, 33, 62] totaling 140,656 hip arthroplasties were pooled to compare the mortality rates within 30 days postoperatively between LVH and HVH. Based on the results of the random meta-analysis model, we found a significantly higher mortality rate in LVH, RR = 2.33 (CI [1.27, 4.28] I 2 = 93%, p value = 0.006) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies [21, 33, 62] totaling 140,656 hip arthroplasties were pooled to compare the mortality rates within 30 days postoperatively between LVH and HVH. Based on the results of the random meta-analysis model, we found a significantly higher mortality rate in LVH, RR = 2.33 (CI [1.27, 4.28] I 2 = 93%, p value = 0.006) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that hospitals performing more treatments of a given type exhibit better outcomes than hospitals performing fewer. This is called the “volume-outcome” relationship and several studies have observed this effect in total hip arthroplasty, where the outcomes of hip arthroplasty in hospitals which perform a higher number of hip arthroplasty procedures annually are better than hospitals which perform a fewer number [2123]. As the current healthcare system endeavors to implement value, centralization of common yet costly surgeries, such as THAs, to high-volume centers of excellence may be an effective way to control the economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed us to control for temporal changes in provider volume over the study period and has been applied elsewhere. 23 We also compiled information on each provider's primary specialization, sex and years since completing his or her basic medical training.…”
Section: Provider and Hospital Characteristicsmentioning
confidence: 99%